Core competencies of the A&E (accident and emergency) nurse in life-threatening situations in the emergency care environment in South Africa - Botha, Annali D.H. (University of Pretoria, 2013)
Dissertation (M Cur (Trauma and Emergency Nursing))--University of Pretoria, 2006.